Ostomy Does Not Lead to Worse Outcomes After Bowel Resection With Ovarian Cancer: A Systematic Review - He, Xinlin; Li, Zhengyu (Frontiers in Oncology, 2022)
Background: Debulking cytoreduction surgery with bowel resection is a common intervention for ovarian cancer. Whether an ostomy should be performed remains controversial. For this study, we performed a meta-analysis and systematic review to determine whether ostomy leads to poorer outcomes for ovarian cancer after bowel resection than anastomosis. Methods: We searched PubMed Medline, Embase, and Cochrane for articles containing the phrase “ovarian cancer with bowel resection,” published between 2016 and 2021. We included studies that compared primary anastomosis with ostomy. We mainly focused on differences in anastomotic leakage (AL) rate, length of hospital stay, 30-day readmission, overall survival, and other survival outcomes between the two procedures. Review Manager V5.3 was used to analyze all studies. Results: Of all 763 studies, three were ultimately included in the meta-analysis (N=1411). Results showed that ostomy might have fewer adverse events of Grade III and above (according to the Clavien–Dindo grade), but the difference was not statistically significant ([Odds ratio] (OR) 0.96 (95% CI [0.75,1.22]). However, ostomy might increase AL, but the difference was not statistically significant (OR 1.07 (95% CI [0.30,3.87]). We did not perform a meta-analysis for other survival outcomes because of differing data types and definitions of these data. We have supplemented the systematic review to include analysis of these data. Conclusion: Ostomy may not result in more AL, but may lead to worse outcomes than anastomosis. However, patients with a more severe ovarian cancer status may be more prone to ostomy rather than primary anastomosis.